Direct K+ and Ag+ Ion-exchanged into SAPO-34 Prepared via Microwave Irradiation and Its Performance in MTO - mazin jasim mohammed; najwa saber majeed (مجلة بغداد للعلوم)
Recently, light olefins became an important material for industrials, especially plastics. High olefins production cost from oil sources, made the researchers look for other methods. Methanol conversion to olefins over SAPOs was an excellent alternative. SAPO-34 molecular sieve is considered a proper catalyst used in this field. For this purpose, SAPO-34 with morpholine template was prepared under microwave irradiation. K and Ag ions were incorporated successfully by ion exchange method. The samples were analyzed by XRD, SEM, EDX, FT-IR, BET, and TGA techniques. XRD showed higher crystallinity of K-SAPO-34 and smaller crystallite size than Ag-SAPO-34. The SEM and EDX analysis indicated perfect distribution of K and Ag metal ions. Surface area reached to 287.64 and 254.59 m2/g for K-SAPO-34 and Ag-SAPO-34, respectively. TGA analysis showed high thermal stability opposite cracking at high temperature of 1100 oC. The catalyst performance on MTO was performed in trickle bed reactor at temperature of 350, 400, 450 and 500 oC at 7.7 hrs-1. The conversion was 100% for the two samples. At 400 oC, olefins selectivity was 85% of K-SAPO-34. Ag-SAPO-34 showed longer lifetime of 475 min with 74% olefins selectivity. Weight hourly space velocity of 15 and 21.1 hrs-1 at 450 oC for K-SAPO-34 were also investigated. As the velocity increased, the conversion and selectivity decreased. It was found that adding K and Ag by ion exchange to SAPO-34 improve surface area and enlarge the pores diffusion. This might hinder the coke deposition in pores and improve olefin selectivity.